The Practice of Assessing the Quality of Student Education: Perspectives from Finland, Canada, and Hong Kong - Obukhova, Tatiana N. (Journal of History Culture and Art Research, 2019)
Critically reviewing the national systems for assessing the quality of education in Finland, Canada, and Hong Kong, the authors consider key issues related to the regulation of quality assessment of general education. The purpose of the study is to analyze foreign practices in the quality assessment regulation (general education) existing in the leading countries in the National Systems Performance Rating. Using the method of content analysis of normative documents, the authors determine the main features of the systems for assessing the quality of general education. They also identify the principles and approaches to assessing the quality of education in the studied countries, which have differences and depend on the goals and objectives of the program that defines the development strategy of the general country-specific education. The authors conclude that the quality assessment focused on the general education is the main criterion for the effectiveness of the functioning and development of the education system in the countries under analysis, and this is reflected in government programs that regulate activities in the field of education. The research also clearly shows that Finland and Canada use softer levers of education management, which give educational institutions more freedom. While in Hong Kong, more “tough” ones are used. In particular, Hong Kong relies on strictly regulated standards and procedures for ensuring the quality of education. The authors state that the practice of regulating the assessment of the quality of education in the studied countries should be taken into account in the development of regulatory and instructive documents governing activities to assess the quality of general education in the Russian Federation.